2022
DOI: 10.1145/3512906
|View full text |Cite
|
Sign up to set email alerts
|

Identifying User Needs for Advertising Controls on Facebook

Abstract: We conducted an online survey and remote usability study to explore user needs related to advertising controls on Facebook and determine how well existing controls align with these needs. Our survey results highlight a range of user objectives related to controlling Facebook ads, including being able to select what ad topics are shown or what personal information is used in ad targeting. Some objectives are achievable with Facebook's existing controls, but participants seemed to be unaware of them, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…In considering these ambiguities, we will use the term 'dark patterns' in a broad sense, regardless of intention, to refer to design patterns that involve inducing certain emotions (e.g., guilt, fear, shame) or misleading mental models (e.g., a misconception of the system or their actions) to manipulate user behaviour towards certain ends-involving mechanisms or goals that the user is unaware of or did not consent to. 6 As noted earlier, the vast majority of literature on dark patterns has focused on how information is phrased or presented in graphic user interfaces (GUIs), most prominently cookie consent banners [5,6,19], ads on online platforms [30,66], and e-commerce websites [44,47,58]. Recently, a handful of papers have started considering dark patterns in the ways that other modalities interact with people, i.e., embodied interactions with robots [33,57], auditory interactions with voice user interfaces (VUIs) [52], and proxemic interactions with movable platforms [28].…”
Section: Distinguishing Nudges Dark and Anti-patternsmentioning
confidence: 99%
“…In considering these ambiguities, we will use the term 'dark patterns' in a broad sense, regardless of intention, to refer to design patterns that involve inducing certain emotions (e.g., guilt, fear, shame) or misleading mental models (e.g., a misconception of the system or their actions) to manipulate user behaviour towards certain ends-involving mechanisms or goals that the user is unaware of or did not consent to. 6 As noted earlier, the vast majority of literature on dark patterns has focused on how information is phrased or presented in graphic user interfaces (GUIs), most prominently cookie consent banners [5,6,19], ads on online platforms [30,66], and e-commerce websites [44,47,58]. Recently, a handful of papers have started considering dark patterns in the ways that other modalities interact with people, i.e., embodied interactions with robots [33,57], auditory interactions with voice user interfaces (VUIs) [52], and proxemic interactions with movable platforms [28].…”
Section: Distinguishing Nudges Dark and Anti-patternsmentioning
confidence: 99%
“…uses data to profile users and serve targeted ads based on such profiles [14]. The data they collect usually consist of both "voluntarily" offered information when signing up, a.o.…”
mentioning
confidence: 99%
“…It has been proven that they can lead to discriminating users [4], spreading fake news [3,21] and creating filter bubbles [12]. Previous studies have shown that people are not always aware of these practices and when they discover them, they often feel uncomfortable with the data that is being collected [6,7,14]. However, a segment of users also considers these targeted ads useful [14,22].…”
mentioning
confidence: 99%
See 2 more Smart Citations